Pencegahan dan Pertolongan Diare di SDN 01 Mersi - Novitasari, Dwi; Yantoro, Awal Tunis; Virjinia, Cahya; Syariefah, Choirina; Yumna, Deziva Maitsa; Anandha, Dhea; Ranjani, Dwi (Yayasan Inspirasi El Burhani, 2024)
Abstract Introduction: Diarrhea is a condition in which there is an increase in the number of bowel movements that occurs as a result of an infection. A child can be said to have experienced diarrhea if the volume of stool is measured greater than 10ml/kg per day. Objective: The aim of this community service was to improve the awareness and health of the in primary school 01 Mersi students. This study aims to prevent and provide first aid for diarrheal diseases in children Method: The method implemented to overcome the problem of diarrhea in elementary school children is by conducting direct counseling on Monday, June 10, 2024 from 07.30-08.30 WIB. The target audience is 5th students at primary school 01 Mersi, with 30 participants. Then, using lecture and discussion methods with media and PowerPoint slides, leaflet,and video about diarrhea, about the importance of Definition of diarrhea, prevention and treatment of diarrhea, symptoms of diarrhea, causes of diarrhea, first aid for diarrhea, how to handle diarrhea. Demonstration about diarrhea using answering questionnaires, lectures, and showing videos about diarrhea and handwashing. The counseling process was conducted group for about an hour. Result: The results are characteristics overview of knowledge of having diarrhea. First, The dominant children aged 11 years and boys 16 people who participated in the counseling. Second, 21 children who have never diarrhea. Conclusion: Diarrhea counseling activities are well organized. There is an increase in childrens knowledge about the importance of maintaining cleanliness to avoid diarrhea.